Portfolio optimization of Malaysian assets with additional cardinality constraint / Muhammad Hazmi Zuraini … [et al.] - Zuraini, Muhammad Hazmi; Shamsul Akmar, Aina Nur Syarah; Azmi, Nor Alia; Maasar, Mohd Azdi (Universiti Teknologi MARA, Negeri Sembilan, 2024)
The main goal of this study is to identify the most effective approach for distributing funds, considering the influence of limitations on the number of assets (cardinality constraints) on reducing risk within a portfolio. We utilise the mean-variance model to evaluate the link between the number of assets in a portfolio and the expected risk-return trade-offs. In addition, we analyse the cardinality-constrained mean-variance (CCMV) model to evaluate its influence on risk for different numbers of investments. We utilise mean-variance analysis to determine the most optimal distribution of investments, with the CCMV model imposing limitations on the number of assets we can invest in and the size of each investment. The Sharpe ratio is employed to evaluate the performance of these models under different constraints, with a higher ratio indicating improved performance. In conclusion, this study emphasises the importance of maintaining a balanced relationship between the potential risks and rewards of investment.